Pelayanan Perubahan Data Pemberitahuan Impor Barang Jalur Hijau Pada Kantor Pelayanan Utama Bea dan Cukai Tipe A Tanjung Priok - Wicaksono, Anggid Aji; Utami, Noviandari Sari (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This observation focuses on the green channel Import Declaration data modification service at the Prime Customs and Excise Office type A Tanjung Priok. The scope of observation includes service processes, constraint identification, and efforts to overcome constraints in service implementation. The observation employed a qualitative approach through six months of observation and interviews with three informants from relevant units. The findings indicate that the service has been digitalized through the implementation of Independent Information Service System (SLIM) and New Generation Employee Administration and Information System (SIAP NG), and have been certified Quality Management System ISO 9001:2015 and Anti-Bribery Management System ISO 37001:2016 with a 12-hour service promise. Data from January to June 2024 shows that from 4,942 applications, 77.6% were approved, 19.3% were returned for revision, and 3.1% were rejected. The main constraints identified include online system disruptions and lengthy cargo position confirmation processes. Handling efforts were conducted through force majeure procedures according to Work Instruction Number ISK/KPU.1/131 Rev.03 and intensive inter-unit coordination. The implications of this observation encourage the need for increased information technology infrastructure capacity and system integration to optimize service quality.